2007
DOI: 10.1007/s11947-007-0035-9
|View full text |Cite
|
Sign up to set email alerts
|

Apple Pectic Gel Produced by Dehydration

Abstract: A novel, flexible sheet-like food formed by the high methoxyl pectin-sugar-acid gelation during drying of apple puree was investigated to characterize drying-related properties. Product volume was reduced by 68% over the process, and this shrinkage was successfully modeled by assuming the volume reduction equal to the volume of water evaporated. The sorption isotherm at 25°C was determined, and a new expression for the moisture content, W, as a function of water activity, a w , of the type W ¼ C 1 exp C 2 a C3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 27 publications
4
23
0
1
Order By: Relevance
“…Since reconstitution is a function of time, and hot water is required in the preparation of soup from okra, it is better to reconstitute it in hot water. However, higher temperatures can adversely affect nutritional properties and organoleptic parameters of rehydrated products (Díaz et al 2008). Using a reconstitution ratio of 1:10 (dried okra/water ratio), reconstituted foam-mat-dried okra was noted to have higher swelling capacity than sun-dried and solar-dried okra.…”
Section: Physical Characteristics Of Dried Powder and Reconstitution mentioning
confidence: 99%
“…Since reconstitution is a function of time, and hot water is required in the preparation of soup from okra, it is better to reconstitute it in hot water. However, higher temperatures can adversely affect nutritional properties and organoleptic parameters of rehydrated products (Díaz et al 2008). Using a reconstitution ratio of 1:10 (dried okra/water ratio), reconstituted foam-mat-dried okra was noted to have higher swelling capacity than sun-dried and solar-dried okra.…”
Section: Physical Characteristics Of Dried Powder and Reconstitution mentioning
confidence: 99%
“…During drying, the apple formulation changes from a fluid-like appearance to a soft paste texture and, finally, to a firm gel. To study the volume variation and the drying kinetic, the initial formulation was placed into acrylic trays (0.18 x 0.138 x 0.013 m), with an initial thickness of 6×10 -3 m, and was dehydrated at 60°C in a forced convection oven, with parallel air flow, to several moisture contents (Leiva Diaz et al, 2009). …”
Section: Restructured Productmentioning
confidence: 99%
“…The Heywood shape factors will be evaluated for the fruits studied in this work, so as to assist in the selection of a suitable geometry to represent the fruits. The case of a restructured fruit product experiencing shrinkage during drying will also be presented, as an example that in all cases it is necessary to evaluate the macro-structural changes (Leiva Diaz, Giannuzzi, & Giner, 2009). On the other hand, experimental data predictions of drying kinetics will be compared according to the type of characteristic dimension used for the products: (a) constant, taken before drying; (b) a value for the partially dehydrated product, depending on the particular study of each product; (c) The characteristic dimension will be calculated by a correlation describing volume changes, to be developed in this work with the aim of being general, valid for the three fruits.…”
Section: Introductionmentioning
confidence: 99%
“…This treatment is considered necessary here since shrinkage is not symmetrical and non-uniform in most foods. Moreover, according to the bibliography (Arnosti et al 2000;Calli Pacco and Menegalli 2004;Leiva Díaz et al 2009;Mowla 2002, 2003;Moreira et al 2000;Ochoa et al 2002aOchoa et al , b, 2007Sjöholm and Gekas 1995;Raghavan and Venkatachalapathy 1999;Ratti 1994;Ratti and Crapiste 2008;Schultz et al 2007) most published shrinkage data are reported to be independent from drying operating conditions or, at most, dependent on air velocity or drying method (Martynenko 2008). On the contrary, evidence suggests that shape changes with velocity and drying method, notably drying rate (Panyawong and Devahastin 2007).…”
Section: Introductionmentioning
confidence: 99%